Empowering diversity: The role of leadership in inclusion in the organizational context - Roque, H. C.; Ramos, M. (Internet of behaviors implementation in organizational contexts, 2023)
Moments of crisis exacerbate social inequalities, highlighting the paramount importance of the debate on inclusion. The promotion of social inclusion can and should be pursued and implemented at various levels. In this sense, leadership can play a fundamental role in the inclusion of individuals in organizations and, consequently, in society. Inclusion in the workplace is about creating an environment where individuals from diverse backgrounds feel valued, respected, and have equal opportunities to contribute and succeed. Leaders have the power to shape the culture, policies, and practices that promote or hinder inclusion. This chapter will review the literature on inclusion based on the responsible leadership and inclusive leadership approaches, seeking to understand how these types of leadership can contribute with effective responses to inclusion in the work context. The chapter will end with a proposal of a set of practices that may be relevant for the inclusion of individuals in organizations.